2022
DOI: 10.1002/sscp.202200117
|View full text |Cite
|
Sign up to set email alerts
|

Analytical reversed‐phase high‐performance liquid chromatography method development for silodosin and solifenacin in bulk and marketed formulation using analytical quality by design approach

Abstract: A reliable HPLC method for the simultaneous estimation of Silodosin and Solifenacin was developed using the quality by design approach. In this study, the main goal was to find a dependable chromatographic system for acceptable component separation. The peaks were sharp within a reasonable run time. For the risk measurement related to the study, critical quality attributes were evaluated.To create an analytical design and a control strategy, the quantitative relationship between critical materials attributes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Design of Experiments (DoE) is employed to systematically study the effects of CMPs on CQAs. The collected data is analyzed using statistical tools, leading to the development of a design space and optimal chromatographic conditions [13][14][15].…”
Section: Evaluation Of the Analytical Methods Employing The Qbd Approachmentioning
confidence: 99%
“…Design of Experiments (DoE) is employed to systematically study the effects of CMPs on CQAs. The collected data is analyzed using statistical tools, leading to the development of a design space and optimal chromatographic conditions [13][14][15].…”
Section: Evaluation Of the Analytical Methods Employing The Qbd Approachmentioning
confidence: 99%
“…The Box-Behnken Design is a helpful technique for improving the outcomes in the field of chromatographic analysis [11,12]. Finding the most important factors that influenced the features of the liquid-liquid chromatographic separation, such as retention time, relative retention time, peak form and symmetry, tailing factor, and the number of theoretical plates, was one of the goals of this study [13][14][15]. A literature survey revealed that several methods are available for the determination of cefepime in different matrixes individually or in combination with other drugs like second-derivative spectroscopy [16], HPLC [17][18][19], and UPLC [20].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature search was conducted to find methods for the analysis of solifenacin succinate and silodosin alone or in combination with other medications. Most of these methods, which include ultraviolet (UV)visible spectrophotometry [10][11][12][13][14][15], spectrofluorometry [15], high-performance liquid chromatography (HPLC) [16][17][18][19][20][21][22][23][24][25][26][27][28], ultra-HPLC [29], liquid chromatography with electrospray ionization mass spectrometry [30], and high-performance thin layer chromatography (HPTLC) [31][32][33]. There is currently no greenness defined analytical method for measuring solifenacin succinate and silodosin in tablet dosage form together.…”
Section: Introductionmentioning
confidence: 99%